La-WO3-CN nano composite material as well as preparation method and application thereof

Through ions and tungsten and tungsten doped modified graphite nitrogen nitride, the LA-WO3-CN nano-composite material is prepared, which solves the problem of poor activity of existing graphite nitrogen nitride. Photo -catalytic degradation effect.

CN119368218APending Publication Date: 2025-01-28JILIN ELECTRIC POWER RES INST LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411645879.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing graphite phase carbon nitride (g-C3N4) photocatalysts have poor photocatalytic activity, mainly due to the weakening of light absorption capacity and the rapid recombination of photogenerated electron-hole pairs.

Method used

By introducing ions and tungsten oxide, mixed with modified graphite nitride nitride, prepare the LA-WO3-CN nano-composite material. This method increases the surface activity site of the material, improves the separation and migration efficiency of the load, and expands the visible light absorption range.

Benefits of technology

A significant improvement of the photocatalytic activity of the LA-WO3-CN nano-composite material, enhancing the absorption of light, and generating more electronics and cave pairs, thereby greatly improving the degradation efficiency of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368218A_ABST
    Figure CN119368218A_ABST
Patent Text Reader

Abstract

The invention discloses a La-WO3-CN nano composite material and a preparation method and application thereof, and belongs to the technical field of semiconductor photocatalysts.By introducing rare earth element lanthanum, the surface hydrophilicity of the La-WO3-CN nano composite material is improved, the carrier separation and migration efficiency is improved, and the photoelectric conversion efficiency is optimized; according to the La-WO3-CN nano composite material disclosed by the invention, the modified graphite phase carbon nitride is doped with the tungsten trioxide, so that the internal impedance of CN-WO3 and the migration resistance of current carriers are reduced, the forbidden bandwidth is reduced, the visible light absorption range of the La-WO3-CN nano composite material is widened, and the light absorption capability is improved, so that more electron and hole pairs are generated, and the activity of the La-WO3-CN nano composite material is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of semiconductor photocatalysts, and in particular to a La-WO3-CN nanocomposite material and a preparation method and application thereof. Background Art

[0002] With the development of industry, environmental problems are becoming increasingly severe. Various persistent organic pollutants are discharged into the environment, which brings huge challenges to traditional pollution control methods. Photocatalysis, as a new advanced oxidation method, uses light energy to generate various oxygen-containing free radicals to effectively degrade or even mineralize difficult-to-degrade pollutants. It is a green and economical pollution control technology with broad application prospects. However, the semiconductor photocatalysts that have been developed so far often have problems such as low light utilization efficiency, serious recombination of photogenerated carriers, and low kinetic rate of interfacial catalytic reactions.

[0003] Graphitic carbon nitride (g-C3N4) is widely used in the field of photocatalysis due to its good physical and chemical stability and easy synthesis. However, pure g-C3N4 photocatalysts show low photocatalytic activity due to the weakening of light absorption capacity caused by the π-π conjugated electron system and the rapid recombination of photogenerated electron-hole pairs. Summary of the invention

[0004] The present invention provides a La-WO3-CN nanocomposite material and a preparation method and application thereof, which effectively solves the technical problem of poor photocatalytic activity when pure g-C3N4 is used as a photocatalyst, and at the same time provides a La-WO3-CN nanocomposite material with large specific surface area, strong visible light absorption capacity and inhibition of photogenerated carrier recombination.

[0005] The first object of the present invention is to provide a La-WO3-CN nanocomposite material, which is prepared by using graphite phase carbon nitride as a carrier and doping modified graphite phase carbon nitride with lanthanum ions and tungsten trioxide.

[0006] As a preferred embodiment, the molar doping amount of lanthanum ions in the La-WO3-CN nanocomposite material is 1% to 2%, and the molar doping amount of tungsten trioxide is 3% to 3.3%.

[0007] As a preferred implementation, the molar doping amount of the lanthanum ions is 2%, and the molar doping amount of tungsten trioxide is 3%.

[0008] The second object of the present invention is to provide a method for preparing the above-mentioned La-WO3-CN nanocomposite material, comprising the following steps:

[0009] preparing respectively a graphite phase carbon nitride alcohol suspension, a tungsten trioxide suspension and a soluble lanthanum salt suspension, mixing the three suspensions, and drying to obtain a mixture;

[0010] The mixture is heated to 380-420°C and calcined. The soluble lanthanum salt is decomposed under high temperature conditions by thermal polycondensation to release lanthanum ions, which are doped with tungsten trioxide into the lattice of graphite phase carbon nitride to obtain La-WO3-CN nanocomposite material.

[0011] As a preferred embodiment, the calcination time is 1.5 to 2.5 hours.

[0012] As a preferred embodiment, the soluble lanthanum salt is lanthanum nitrate, lanthanum acetate or lanthanum chloride.

[0013] As a preferred implementation, the heating rate is 2-10°C / min.

[0014] As a preferred embodiment, the alcohol suspension of graphite phase carbon nitride is specifically obtained by dispersing graphite phase carbon nitride powder in ethanol solution; the tungsten trioxide suspension is specifically obtained by dispersing tungsten trioxide powder in deionized water, adding a dispersant, and stirring evenly; the soluble lanthanum salt suspension is specifically obtained by dispersing soluble lanthanum salt powder in deionized water.

[0015] As a preferred embodiment, a crude product is obtained by a thermal polycondensation method, the crude product is ground, washed with ethanol and deionized water, filtered, and dried to obtain a La-WO3-CN nanocomposite material.

[0016] The third object of the present invention is to provide an application of the La-WO3-CN nanocomposite material in photocatalytic degradation of organic pollutants.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The present invention prepares a La-WO3-CN nanocomposite material by doping modified graphite phase carbon nitride with lanthanum ions and tungsten trioxide, increases the active sites exposed on the surface of graphite phase carbon nitride, and reduces the diffusion distance of photogenerated charge carriers. The present invention increases the surface hydrophilicity of the La-WO3-CN nanocomposite material by introducing the rare earth element lanthanum, improves the carrier separation and migration efficiency, and optimizes the photoelectric conversion efficiency; by doping modified graphite phase carbon nitride with tungsten trioxide, the internal impedance of CN-WO3 and the migration resistance of carriers are reduced, the bandgap width is reduced, the visible light absorption range of the La-WO3-CN nanocomposite material is widened, and the light absorption capacity is improved, thereby generating more electron and hole pairs, and then greatly improving the activity of the La-WO3-CN nanocomposite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1It is a Fourier transform infrared spectra of the La-WO3-CN nanocomposite materials prepared in Examples 1 to 3 of the present invention and the CN-WO3 composite material prepared in Comparative Example 1.

[0020] Figure 2 XRD spectra of the La-WO3-CN nanocomposite materials prepared in Examples 1 to 3 of the present invention, the CN-WO3 composite materials prepared in Comparative Example 1, and the pure g-C3N4 in Comparative Example 2.

[0021] Figure 3 Solid ultraviolet diffuse reflectance spectra of the La-WO3-CN nanocomposite materials prepared in Examples 1 to 3 of the present invention, the CN-WO3 composite materials prepared in Comparative Example 1, and the pure g-C3N4 in Comparative Example 2.

[0022] Figure 4 Graph showing the corresponding bandgap widths of the CN-WO3 and x-La-WO3-CN (x is 5, 10 and 15) composites prepared in Examples 1 to 3 of the present invention.

[0023] Figure 5 The photoluminescence spectra of the La-WO3-CN nanocomposite materials prepared in Examples 1 to 3 of the present invention, the CN-WO3 composite materials prepared in Comparative Example 1, and the pure g-C3N4 in Comparative Example 2 are shown.

[0024] Figure 6 Electrochemical impedance spectra of the La-WO3-CN nanocomposites prepared in Examples 1 to 3 of the present invention and the CN-WO3 composite material prepared in Comparative Example 1.

[0025] Figure 7 The photocurrent response curves of the La-WO3-CN nanocomposites prepared in Examples 1 to 3 of the present invention and the CN-WO3 composite material prepared in Comparative Example 1 are shown.

[0026] Figure 8 This is a Mott-Schottky test curve diagram of the La-WO3-CN nanocomposite materials prepared in Examples 1 to 3 of the present invention and the CN-WO3 composite material prepared in Comparative Example 1.

[0027] Fig. 9 The photocatalytic degradation rate curve of Rhodamine B of the La-WO3-CN nanocomposite prepared in Examples 1 to 3 of the present invention, the CN-WO3 composite material prepared in Comparative Example 1, and the pure g-C3N4 in Comparative Example 2 is shown. DETAILED DESCRIPTION

[0028] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific examples, but the examples are not intended to limit the present invention. The following test methods and detection methods, unless otherwise specified, are conventional methods; the reagents and raw materials, unless otherwise specified, are commercially available.

[0029] The background technology of the present invention mentions that the existing graphite phase carbon nitride (g-C3N4) has a problem that the pure g-C3N4 photocatalyst shows low photocatalytic activity due to the weakened light absorption ability of the π-π conjugated electron system and the rapid recombination of photogenerated electron-hole pairs. Based on the above technical problems, the present invention provides a La-WO3-CN nanocomposite material and a preparation method and application thereof, and a La-WO3-CN nanocomposite material is prepared by doping modified graphite phase carbon nitride with lanthanum ions and tungsten trioxide.

[0030] The technical solution of the present invention is analyzed and explained in detail below.

[0031] The present invention firstly provides a La-WO3-CN nanocomposite material, which is prepared by taking graphite phase carbon nitride as a carrier and doping and modifying the graphite phase carbon nitride with lanthanum ions and tungsten trioxide.

[0032] In the above technical scheme, the surface hydrophilicity of the La-WO3-CN nanocomposite material is increased by introducing the rare earth element lanthanum, the carrier separation and migration efficiency are improved, and the photoelectric conversion efficiency is optimized; the graphite phase carbon nitride is modified by doping tungsten trioxide to reduce the internal impedance of CN-WO3 and the migration resistance of carriers, and the band gap width is reduced, so that the visible light absorption range of the La-WO3-CN nanocomposite material is widened, and the light absorption capacity is improved, thereby generating more electron and hole pairs, and then greatly improving the activity of the La-WO3-CN nanocomposite material.

[0033] As a preferred embodiment, the molar doping amount of lanthanum ions in the La-WO3-CN nanocomposite material is 1% to 2%, and the molar doping amount of tungsten trioxide is 3% to 3.3%. In the preparation of the La-WO3-CN nanocomposite material, the amount ratio of graphite phase carbon nitride, tungsten trioxide and soluble lanthanum salt is 0.17g:15mg:15.39 to 46.17μmol. In the photocatalytic reaction, the lanthanum doping amount in the tungsten oxide-lanthanum nitrate-carbon nitride system has a significant effect on the catalytic performance. When the amount of soluble lanthanum salt is less than 15.39μmol, the doping amount is insufficient. When the lanthanum doping amount is too low, the electronic structure and energy band structure of the tungsten oxide-carbon nitride composite material cannot be effectively changed, thereby failing to significantly improve its photocatalytic performance; insufficient lanthanum doping can also lead to limited improvement in the separation efficiency and mobility of photogenerated carriers, thereby affecting the efficiency of the photocatalytic reaction. When the dosage of soluble lanthanum salt is greater than 46.17 μmol, the lanthanum doping amount is too high, and the "doping saturation" phenomenon occurs, that is, too many doped ions become the recombination centers of photogenerated carriers, reducing the photocatalytic activity; excessive lanthanum doping will also cause changes in the light absorption properties of the photocatalyst, such as redshift or blueshift of the absorption sideband; high doping levels also affect the structural stability and phase purity of the photocatalyst; too many doped ions will introduce new phases or cause increased lattice distortion, thereby affecting the catalytic performance and service life of the photocatalyst.

[0034] In order to obtain the best catalytic performance, the molar doping amount of the lanthanum ion is 2%, and the molar doping amount of tungsten trioxide is 3%. During the preparation, the amount ratio of graphite phase carbon nitride, tungsten trioxide and soluble lanthanum salt is 0.17g:15mg:30.78μmol.

[0035] The present invention also provides a method for preparing a La-WO3-CN nanocomposite material, comprising the following steps:

[0036] Prepare respectively an alcohol suspension of graphite phase carbon nitride (dispersing graphite phase carbon nitride powder in an ethanol solution), a tungsten trioxide suspension (dispersing tungsten trioxide powder in deionized water, adding a dispersant, and stirring evenly), and a soluble lanthanum salt suspension (dispersing soluble lanthanum salt powder in deionized water), mix well, and dry to obtain a mixture; the soluble lanthanum salt can be selected from lanthanum nitrate, lanthanum acetate or lanthanum chloride.

[0037] Preparation of graphite phase carbon nitride: It is prepared by thermal polymerization using urea as a nitrogen-rich precursor. First, 10 g of urea is placed in a 50 mL crucible, and the crucible is tightly covered with a lid of the same specification, and placed in a muffle furnace for heating. The initial temperature is 20°C, and the temperature is raised to 520°C in 100 minutes and kept constant for 2 hours, then naturally cooled to room temperature. The prepared solid is light yellow. Next, the solid is fully ground into powder, and then washed several times with deionized water and anhydrous ethanol, respectively, and finally dried in an oven to obtain graphite phase carbon nitride, abbreviated as g-C3N4.

[0038] Preparation of tungsten trioxide: Sodium tungstate dihydrate (Na2WO4·2H2O) was used as a precursor and prepared by acid induction and hydrothermal synthesis. 1.32g sodium tungstate and 1.17g sodium chloride were weighed and added to a 100mL beaker, and then 40mL deionized water was added. While stirring, 10% hydrochloric acid solution was gradually dripped to adjust the pH of the solution. The colorless solution gradually turned into a light yellow colloid. Subsequently, 300mg oxalic acid was added and stirred for 30min. Then, the reaction container was placed in a 180℃ water bath and heated for several hours. After hydrothermal treatment, it was washed with anhydrous ethanol and deionized water for several times, placed in an oven to dry and grind to obtain tungsten trioxide.

[0039] The mixture is heated to 380-420° C. and calcined. Through a thermal polycondensation method, the soluble lanthanum salt is decomposed under high temperature conditions to release lanthanum ions, which are doped with tungsten trioxide into the lattice of graphite phase carbon nitride to obtain a La-WO3-CN nanocomposite material.

[0040] In order to obtain a La-WO3-CN nanocomposite material with optimal performance, the calcination time is 1.5 to 2.5 hours. Appropriate calcination conditions can optimize the crystal structure. In the temperature range of 380 to 420°C, especially the optimal 400°C, the crystal structure of carbon nitride, tungsten trioxide and soluble lanthanum salt can be effectively optimized to form a more stable and favorable phase state, thereby improving its physical and chemical properties. Promote chemical reactions. Appropriate calcination temperatures can promote chemical reactions between raw materials, so that carbon nitride, tungsten oxide and soluble lanthanum salt can be more fully converted into target products, thereby improving the purity and yield of the products. Avoid the formation of impurities. Under appropriate calcination conditions, the formation of impurities can be avoided or reduced to ensure the quality of the product. Save energy. Selecting the optimal calcination temperature can maximize energy conservation and reduce production costs while ensuring product quality. If the calcination conditions of the present invention are not adopted, the composite material will have poor performance due to insufficient or excessive calcination. Insufficient calcination will result in an incomplete crystal structure, and a calcination temperature that is too low will result in the inability to fully form a crystal structure, affecting the physical and chemical properties of the product. Insufficient chemical reaction: The chemical reaction between the raw materials cannot be fully carried out, resulting in low product purity and poor yield. The impurity content is high, and low-temperature calcination cannot effectively remove impurities in the raw materials, affecting the quality of the product. Excessive calcination will cause the crystal structure to be destroyed. Excessive calcination temperature will cause the crystal structure to be destroyed, resulting in a decrease in product performance. Product decomposition: At high temperatures, carbon nitride, tungsten oxide, and soluble lanthanum salts undergo decomposition reactions to generate unwanted by-products, reducing the purity and yield of the product. Increased energy consumption: Excessively high calcination temperatures will increase energy consumption and increase production costs.

[0041] In order to further improve the performance of the composite material, the heating rate is 2 to 10 ° C / min. In some photocatalytic materials, the heating rate will affect its crystal structure and crystallinity, thereby affecting its photocatalytic performance. First, it affects the specific surface area: Generally speaking, when the heating rate is low, more holes may be formed on the surface of the material, thereby increasing the specific surface area. The increase in specific surface area helps to improve the adsorption capacity of the photocatalyst for reactants, thereby improving its photocatalytic performance. However, too high a heating rate may cause the surface of the material to be too dense, reduce the specific surface area, and be detrimental to the improvement of photocatalytic performance. Second, it affects the pore size distribution and dispersion: at a low heating rate, the pore size distribution of the catalyst is narrow and the pore size is more uniform, which is conducive to the diffusion and transmission of reactants during the photocatalytic reaction. At the same time, a low heating rate also helps to improve the dispersion of the catalyst, making the catalyst particles more evenly distributed, thereby improving the photocatalytic performance. On the contrary, at a high heating rate, the pore size distribution of the catalyst may become wider and uneven, and the dispersion of the catalyst particles may also be affected, thereby reducing the photocatalytic performance. Third, the rate of photocatalytic reaction: The heating rate may also indirectly affect the photocatalytic performance by affecting the photocatalytic reaction mechanism. For example, in some photocatalytic reactions, the heating rate may change the adsorption state of the reactants, the concentration or type of surface reactive species, etc., thereby affecting the photocatalytic reaction rate.

[0042] As a preferred embodiment, the alcohol suspension of graphite phase carbon nitride is specifically obtained by dispersing graphite phase carbon nitride powder in ethanol solution; the tungsten trioxide suspension is specifically obtained by dispersing tungsten trioxide powder in deionized water, adding a dispersant, and stirring evenly; the soluble lanthanum salt suspension is specifically obtained by dispersing soluble lanthanum salt powder in deionized water.

[0043] As a preferred embodiment, after grinding, the mixture is washed with ethanol and deionized water, filtered, and dried to obtain a La-WO3-CN nanocomposite material.

[0044] The technical effects of the present invention are described in detail below through specific embodiments and comparative examples.

[0045] Example 1

[0046] A method for preparing a La-WO3-CN nanocomposite material, characterized in that it comprises the following steps:

[0047] S1, 0.17 g of g-C3N4 powder was dispersed in 30 mL of ethanol, stirred for 30 min, and further ultrasonicated for 30 min to form a g-C3N4 suspension.

[0048] S2, disperse 15 mg of WO3 powder into 30 mL of deionized water, add 1 mL of 5% PEG-400 as a dispersant, and continue stirring for 30 minutes to obtain a WO3 suspension.

[0049] S3, disperse 5 mg of La(NO3)3 powder into 30 ml of deionized water and continue stirring for 30 minutes to obtain a La(NO3)3 suspension.

[0050] S4, transfer the suspension of g-C3N4 and the suspension of La(NO3)3 into a beaker containing the WO3 suspension, stir for 12 hours to obtain a mixed suspension, dry the mixed suspension in a 60°C oven, then heat to 400°C in a muffle furnace at a rate of 5°C / min, keep warm for 2 hours, and finally cool to room temperature. The obtained sample is washed and filtered three times with ethanol and deionized water, dried in an oven and ground to obtain a La-WO3-CN nanocomposite material, recorded as 5-La-WO3-CN composite.

[0051] Example 2

[0052] A method for preparing a La-WO3-CN nanocomposite material, characterized in that it comprises the following steps:

[0053] S1, 0.17 g of g-C3N4 powder was dispersed in 30 mL of ethanol, stirred for 30 min, and further ultrasonicated for 30 min to form a g-C3N4 suspension.

[0054] S2, disperse 15 mg of WO3 powder into 30 mL of deionized water, add 1 mL of 5% PEG-400 as a dispersant, and continue stirring for 30 minutes to obtain a WO3 suspension.

[0055] S3, disperse 10 mg of La(NO3)3 powder into 30 ml of deionized water and continue stirring for 30 minutes to obtain a La(NO3)3 suspension.

[0056] S4, transfer the suspension of g-C3N4 and the suspension of La(NO3)3 into a beaker containing the WO3 suspension, stir for 12 hours to obtain a mixed suspension, dry the mixed suspension in a 60°C oven, then heat to 400°C in a muffle furnace at a rate of 5°C / min, keep warm for 2 hours, and finally cool to room temperature. The obtained sample is washed and filtered three times with ethanol and deionized water, dried in an oven and ground to obtain a La-WO3-CN nanocomposite material, recorded as 10-La-WO3-CN composite.

[0057] Example 3

[0058] A method for preparing a La-WO3-CN nanocomposite material, characterized in that it comprises the following steps:

[0059] S1, 0.17 g of g-C3N4 powder was dispersed in 30 mL of ethanol, stirred for 30 min, and further ultrasonicated for 30 min to form a g-C3N4 suspension.

[0060] S2, disperse 15 mg of WO3 powder into 30 mL of deionized water, add 1 mL of 5% PEG-400 as a dispersant, and continue stirring for 30 minutes to obtain a WO3 suspension.

[0061] S3, disperse 15 mg of La(NO3)3 powder into 30 ml of deionized water and continue stirring for 30 minutes to obtain a La(NO3)3 suspension.

[0062] S4, transfer the suspension of g-C3N4 and the suspension of La(NO3)3 into a beaker containing the WO3 suspension, stir for 12 hours to obtain a mixed suspension, dry the mixed suspension in a 60°C oven, then heat to 400°C in a muffle furnace at a rate of 5°C / min, keep warm for 2 hours, and finally cool to room temperature. The obtained sample is washed and filtered three times with ethanol and deionized water, dried in an oven and ground to obtain a La-WO3-CN nanocomposite material, recorded as 15-La-WO3-CN composite.

[0063] In order to further illustrate the technical effect of the present invention, the present invention also sets a comparative example, which is as follows:

[0064] Comparative Example 1

[0065] Compared with Example 1, the difference is that the rare earth element La is not introduced.

[0066] A method for preparing a CN-WO3 composite material, characterized by comprising the following steps:

[0067] S1, 0.17 g of g-C3N4 powder was dispersed in 30 mL of ethanol, stirred for 30 min, and further ultrasonicated for 30 min to form a g-C3N4 suspension.

[0068] S2, disperse 15 mg of WO3 powder into 30 mL of deionized water, add 1 mL of 5% PEG-400 as a dispersant, and continue stirring for 30 minutes to obtain a WO3 suspension.

[0069] S3, transfer the g-C3N4 suspension into a beaker containing WO3 suspension, stir for 12 hours to obtain a mixed suspension, dry the mixed suspension in a 60°C oven, then heat to 400°C in a muffle furnace at a rate of 5°C / min, keep warm for 2 hours, and finally cool to room temperature. The obtained sample is washed and filtered three times with ethanol and deionized water, dried in an oven and ground to obtain a CN-WO3 composite material (CN-WO3 composite).

[0070] Comparative Example 2

[0071] Pure g-C3N4.

[0072] The performance test results of the La-WO3-CN nanocomposite material prepared in the embodiment of the present invention and the CN-WO3 composite material prepared in Comparative Example 1 are as follows.

[0073] Figure 1 The Fourier transform infrared spectra of the 5-La-WO3-CN composite prepared in Example 1 of the present invention, the 10-La-WO3-CN composite prepared in Example 2, the 15-La-WO3-CN composite prepared in Example 3, and the CN-WO3 composite prepared in Comparative Example 1 are shown. Figure 1 It can be seen that after rare earth metal La doping, there is no obvious difference in the infrared spectra of CN-WO3 composites and x-La-WO3-CN composites, and the peak positions of all samples are the same, which confirms that a small amount of doping does not change the chemical structure of g-C3N4. -1 The wave number at 1200 cm corresponds to the absorption peak of the heptazine ring of the g-C3N4 basic structure. -1 To 1650cm -1 The region is the stretching vibration of CN or C=N aromatic heterocyclic ring in g-C3N4. -1 The broad absorption band between corresponds to the stretching vibration of the residual NH and OH bonds, which is related to the uncondensed amino groups and the absorbed oxygen-containing species. The x-La-WO3-CN composite shows all the characteristic peaks of pure CN, indicating that carbon nitride exists in the sample prepared by thermal polycondensation and the functional groups are not destroyed.

[0074] Figure 2 The XRD spectra of the 5-La-WO3-CN composite prepared in Example 1, the 10-La-WO3-CN composite prepared in Example 2, the 15-La-WO3-CN composite prepared in Example 3, the CN-WO3 composite and pure g-C3N4 are shown in FIG. Figure 2It can be seen that in the x-La-WO3-CN composite material, the characteristic peaks of x-La-WO3-CN and CN-WO3 can be detected, which means that La is successfully loaded on the CN-WO3 surface. A typical g-C3N4 phase diffraction pattern is shown at 13.0° and 27.4°, showing two diffraction peaks. The diffraction peak at 13.0° corresponds to the (100) surface of the repeated heptazine structural unit in the two-dimensional plane, and the strong peak at 27.4° corresponds to the (002) crystal plane of the conjugated aromatic structure stacked between the g-C3N4 layers, highlighting the formation of the graphite phase structure. The strong diffraction peaks at 22.7°, 24.3°, 28.2°, 33.6°, 36.6°, 49.6°, and 55.4° correspond to the (001), (110), (101), (200), (111), (201), (112), and (331) crystal planes of tungsten (VI) oxide, respectively. In all synthesized x-La-CN-WO3 heterostructures, the XRD pattern has the combined characteristics of WO3 and g-C3N4 components, showing typical peaks corresponding to g-C3N4 and WO3, confirming the coexistence of WO3 and g-C3N4 in the composite material. After CN-WO3 is doped with the rare earth element La, the position of the peaks is almost unchanged, but the peak width is slightly wider.

[0075] Figure 3 Solid UV diffuse reflectance spectra of x-La-WO3-CN (x is 5, 10 and 15) composites, CN-WO3 composites and pure g-C3N4 prepared in Examples 1, 2 and 3 of the present invention, Figure 4 The corresponding bandgap width diagram of the CN-WO3 and x-La-WO3-CN (x is 5, 10 and 15) composites prepared in Examples 1, 2 and 3 of the present invention. Figure 3 It can be seen that after the WO3-CN complex is doped with La, the visible light response range is slightly red-shifted. This shows that the introduction of the rare earth element La can reduce the band gap width of CN-WO3, widen the visible light absorption range of the photocatalyst, thereby improving the light absorption capacity, and then generating more electron and hole pairs, thereby greatly improving the activity of the photocatalyst. The band gap energy of CN-WO3 and x-La-WO3-CN complexes is calculated according to the Kubelka-Munk formula, and the corresponding Tauc diagram is obtained, which is Figure 4 It can be seen that the band gap energy E g It gradually becomes smaller (2.66eV>2.61eV) and the bandgap width narrows.

[0076] Figure 5Photoluminescence spectra of the 5-La-WO3-CN composite prepared in Example 1 of the present invention, the 10-La-WO3-CN composite prepared in Example 2, the 15-La-WO3-CN composite prepared in Example 3, the CN-WO3 composite, and pure g-C3N4. From Figure 5 As can be seen from Figure 5 , the high PL emission intensity of CN-WO3 means that the recombination rate of photo-generated electrons is relatively high. After combining with the rare earth element La, the intensity of the PL peak is significantly weakened, and the recombination of photo-generated carriers in CN-WO3 is effectively inhibited, indicating that the combination of an appropriate amount of La and CN-WO3 improves the charge separation efficiency, and the electron-hole pairs generated by light illumination are more effectively separated and transferred, which helps to improve the photocatalytic performance.

[0077] Figure 6 Electrochemical impedance spectra of the 5-La-WO3-CN composite prepared in Example 1 of the present invention, the 10-La-WO3-CN composite prepared in Example 2, the 15-La-WO3-CN composite prepared in Example 3, and the CN-WO3 composite. From Figure 6 As can be seen from Figure 6 , the radius of the semicircle of the samples is 10La-CN-WO3 < CN-WO3 < g-C3N4. Compared with CN-WO3, the slope of the x-La-WO3-CN composite material decreases, and the impedance decreases to a certain extent. This shows that the introduction of the rare earth element La reduces the internal impedance of CN-WO3 and the migration resistance of carriers, indicating that the modified sample has a smaller diffusion resistance.

[0078] Figure 7 Photocurrent response curves of the 5-La-WO3-CN composite prepared in Example 1 of the present invention, the 10-La-WO3-CN composite prepared in Example 2, the 15-La-WO3-CN composite prepared in Example 3, and the CN-WO3 composite. From Figure 7 As can be seen from Figure 7 , compared with CN-WO3, the periodic photocurrent density of the x-La-WO3-CN composite material increases, the charge transfer efficiency improves, and the separation effect of electron-hole pairs is enhanced, which is beneficial to photocatalytic activity. This shows that the introduction of the rare earth element La improves the migration ability and generation ability of photo-excited electrons to varying degrees.

[0079] Figure 8 Mott-Schottky test curves of the 5-La-WO3-CN composite prepared in Example 1 of the present invention, the 10-La-WO3-CN composite prepared in Example 2, the 15-La-WO3-CN composite prepared in Example 3, and the CN-WO3 composite. From Figure 8It can be seen that the tangent slopes of the x-La-WO3-CN composite and CN-WO3 composite samples are both positive, which means that they are both N-type semiconductors and electrons are the main carriers. The Mott-Schottky plot of x-La-CN-WO3 shows a smaller slope than that of g-C3N4, indicating that the electron donor density of the x-La-CN-WO3 heterostructure is higher. The high donor density helps to increase the conductivity and charge carrier mobility and improve the photocatalytic performance. This shows that the introduction of rare earth element La can effectively improve the photocatalytic degradation activity.

[0080] Fig. 9 The photocatalytic degradation rate curves of Rhodamine B by the 5-La-WO3-CN complex prepared in Example 1, the 10-La-WO3-CN complex prepared in Example 2, the 15-La-WO3-CN complex prepared in Example 3, the CN-WO3 complex and the pure g-C3N4 of Comparative Example 2 are shown. Fig. 9 It can be seen that the degradation rates of all synthesized x-La-WO3-CN (x is 5, 10 and 15) photocatalysts are higher than those of CN-WO3 photocatalyst and pure g-C3N4 photocatalyst, indicating that the introduction of rare earth element La can effectively improve the photocatalytic degradation activity. With the increase of the rare earth element La content, the photocatalytic degradation rate first increases and then decreases, indicating the regulatory effect of the rare earth element La content on the degradation performance. The degradation rate of the 10-La-WO3-CN composite is the highest, that is, the optimal doping amount of the composite rare earth element La is 10 mg. Regarding the degradation of Rhodamine B, the degradation rate of the composite material prepared by the present invention for 40 minutes of light reaction reaches 98.6%, which is 15.4 times higher than that of pure g-C3N4 and 1.5 times higher than that of CN-WO3, and has good photocatalytic performance.

[0081] In summary, the present invention prepares La-WO3-CN composite photocatalyst by doping modified graphite phase carbon nitride with rare earth elements lanthanum and tungsten trioxide. The introduction of rare earth element La increases the specific surface area of ​​the nanocomposite material, improves the hydrophilicity, and promotes the separation and migration of photogenerated charge carriers, thereby improving the photocatalytic performance.

[0082] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A La-WO3-CN nanocomposite material, characterized in that: The invention adopts graphite phase carbon nitride as carrier and is prepared by doping modified graphite phase carbon nitride with lanthanum ions and tungsten trioxide.

2. The La-WO3-CN nanocomposite material according to claim 1, characterized in that: The molar doping amount of lanthanum ions in the La-WO3-CN nanocomposite material is 1% to 2%, and the molar doping amount of tungsten trioxide is 3% to 3.3%.

3. The La-WO3-CN nanocomposite material according to claim 2, characterized in that: The molar doping amount of the lanthanum ions is 2%, and the molar doping amount of tungsten trioxide is 3%.

4. A method for preparing the La-WO3-CN nanocomposite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: preparing respectively a graphite phase carbon nitride alcohol suspension, a tungsten trioxide suspension and a soluble lanthanum salt suspension, mixing the three suspensions, and drying to obtain a mixture; The mixture is heated to 380-420° C. and calcined. The soluble lanthanum salt is decomposed under high temperature conditions by a thermal polycondensation method to release lanthanum ions, which are doped with tungsten trioxide into the lattice of graphite phase carbon nitride to obtain a La-WO3-CN nanocomposite material.

5. The preparation method according to claim 4, characterized in that: The calcination time is 1.5 to 2.5 hours.

6. The preparation method according to claim 4, characterized in that: The soluble lanthanum salt is lanthanum nitrate, lanthanum acetate or lanthanum chloride.

7. The preparation method according to claim 4, characterized in that: The heating rate is 2-10°C / min.

8. The preparation method according to claim 4, characterized in that: The alcohol suspension of graphite phase carbon nitride is specifically prepared by dispersing graphite phase carbon nitride powder in ethanol solution; the tungsten trioxide suspension is specifically prepared by dispersing tungsten trioxide powder in deionized water, adding a dispersant, and stirring evenly; the soluble lanthanum salt suspension is specifically prepared by dispersing soluble lanthanum salt powder in deionized water.

9. The preparation method according to claim 4, characterized in that: A crude product is obtained by a thermal polycondensation method, and the crude product is ground, washed with ethanol and deionized water, filtered, and dried to obtain a La-WO3-CN nanocomposite material.

10. Use of the La-WO3-CN nanocomposite material according to any one of claims 1 to 3 in photocatalytic degradation of organic pollutants.

Citation Information

Cited By

  • Particulate crystalline nanocomposite as a sorbent for wastewater treatment

    US12491489B1